2013
DOI: 10.7235/hort.2013.12229
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Resveratrol Biosynthesis in Grape Skins and Leaves by Ultrasonication Treatment

Abstract: Abstract. Grapes (Vitis vinifera) are one of the most important fruits worldwide and are eaten raw or after conversion to jelly, jam, juice and wine. Grape skins are a major source of resveratrol (3,5,4′-trihydroxystilbene), which has the ability to reduce blood sugar as well as anticancer, anti-inflammatory, and other beneficial cardiovascular effects. In this study, we investigated the increased accumulation of resveratrol in grape skin and leaves following ultrasonication treatment, which has been shown to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Comarella et al (2012) in their study on the effects of US application in grapes suggested that an 83% increase in phenolic compounds in the juice were due to the elicitor effect of US. Hasan and Baek (2013) also demonstrated that application of US in grapes led to trans-resveratrol accumulation in the fruit peel. This result was positively correlated with the increase in the expression of resveratrol synthase gene, suggesting that upregulation of the gene and the consequent increase in the enzyme activity by US treatment was responsible for the increase in trans-resveratrol content.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Comarella et al (2012) in their study on the effects of US application in grapes suggested that an 83% increase in phenolic compounds in the juice were due to the elicitor effect of US. Hasan and Baek (2013) also demonstrated that application of US in grapes led to trans-resveratrol accumulation in the fruit peel. This result was positively correlated with the increase in the expression of resveratrol synthase gene, suggesting that upregulation of the gene and the consequent increase in the enzyme activity by US treatment was responsible for the increase in trans-resveratrol content.…”
Section: Resultsmentioning
confidence: 87%
“…Previous studies have shown that postharvest application of US increased the content of phenolic substances in peanuts (RUDOLF; RESURRECCION, 2005;SALES;RESURRECCION, 2009) and romaine lettuce (YU et al, 2016). Few studies on grapes have demonstrated the effect of US in increasing resveratrol production in the fruit BAEK, 2013), as well as the enrichment of the juice and other phenolic substances (HASAN et al, 2014;COMARELLA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…13) (Hasan and Baek 2013). A significantly higher amount of E-resveratrol over that in the control sample was observed following ultrasonication treatment.…”
Section: Abiotic Postharvest Treatments Of Grapementioning
confidence: 90%
“…Most of recent studies found a higher resveratrol concentration achieved when peanuts treated with ultrasound using different parameters [10,28]. In addition, ultrasound has been used to increase resveratrol content in fruits, such as grape skin and grape juice [12,29]. Therefore, in this study we applied the ultrasound treatment to prepare resveratrol-enriched peanut sprout using different peanut varieties.…”
Section: Effect Of Ultrasound Treatment On Resveratrol Content In Peamentioning
confidence: 99%